The influence of in-plane anisotropy and temperature on the performance of AA2050-T84 alloy - Ekabote Nagaraj (FME Transactions)
AA2050-T84 alloy is a third-generation Al-Li alloy used in aircraft and space vehicles. The spars and ribs of aircraft wings and fuel tanks of space shuttle tanks must possess damage tolerance properties. In this work, the tensile and fracture test specimens were extracted from the principal directions of the 43 mm-thick AA2050-T84 alloy plate and experimentally investigated at -50°C, 24°C, and 150°C. The dependency of tensile and fracture toughness properties on in-plane anisotropy and test temperature was observed. Also, the in-plane anisotropy effect on crack initiation, propagation, and deviations from principal crack directions under Mode-I loading was discussed. The short transverse directional tensile and fracture toughness properties were lowest due to weakened grain boundaries originating from the T-84 state. Further, the effect of the in-plane anisotropy nature of the alloy on the extraction of aircraft wing components is discussed.